Reactive Eccrine Syringofibroadenoma on the Heel, Clinically Mimicking Squamous Cell Carcinoma - Yuri Sugita; Teruhiko Makino; Kotaro Matsui; Tadamichi Shimizu (Case Reports in Dermatological Medicine)
The authors present a case of eccrine syringofibroadenoma that clinically mimicked squamous cell carcinoma and briefly comment on the current knowledge about its clinical and histopathological features and therapeutic options.